2018
DOI: 10.1099/jmm.0.000717
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of Streptococcus pneumoniae isolates from invasive disease in adults following the introduction of PCV10 in Brazil

Abstract: Our data suggest a predominance of non-PCV10 serotypes among IPD in the elderly population in circulating strains ca. 3 to 5 years after the introduction of PCV10 in Brazil.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…Although emergence of this serotype after PCV7 introduction in certain high-income countries is a well-established fact (Isaacman et al, 2010; Isturiz et al, 2017), serotype 19A emergence after PCV10 introduction in Brazil still seems to be a contradictory issue. While certain studies reveal that occurrence of this serotype has not significantly changed (Medeiros et al, 2017; Neves et al, 2018), others report an increasing rate (Cassiolato et al, 2018; Christophe et al, 2018). We also observed that serotypes 3, 8, 20, and 23A emerged among isolates from IPD cases, whereas serotypes 6C, 35B, and NT isolates were more commonly associated with asymptomatic carriage.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Although emergence of this serotype after PCV7 introduction in certain high-income countries is a well-established fact (Isaacman et al, 2010; Isturiz et al, 2017), serotype 19A emergence after PCV10 introduction in Brazil still seems to be a contradictory issue. While certain studies reveal that occurrence of this serotype has not significantly changed (Medeiros et al, 2017; Neves et al, 2018), others report an increasing rate (Cassiolato et al, 2018; Christophe et al, 2018). We also observed that serotypes 3, 8, 20, and 23A emerged among isolates from IPD cases, whereas serotypes 6C, 35B, and NT isolates were more commonly associated with asymptomatic carriage.…”
Section: Discussionmentioning
confidence: 97%
“…We also observed that serotypes 3, 8, 20, and 23A emerged among isolates from IPD cases, whereas serotypes 6C, 35B, and NT isolates were more commonly associated with asymptomatic carriage. Emergence of serotype 6C in carriage and of serotypes 3 and 8 in IPD after PCV10 implementation in Brazil has been recently described (Medeiros et al, 2017; Christophe et al, 2018; Neves et al, 2018). Of note, all these emerging non-PCV10 serotypes have been circulating in our setting since the 1990s, reinforcing the possibility of serotype replacement phenomenon.…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted in the city of Porto Alegre, Brazil, 3–4 years after PCV10 introduction (2013–2015) among invasive strains from adults ≥50 years identified 10 strains belonging to ST320 among 13 invasive Spn19A strains [28].…”
Section: Discussionmentioning
confidence: 99%
“…The characterization of Spn19A from Brazil has been described only in independent studies, each with a limited number of Spn19A strains isolated [2830]. In a recent report, using data from Brazilian laboratory-based surveillance, nonvaccine types increased, with Spn19A being the most prevalent cause of IPD after four years of PCV10 use [31].…”
Section: Introductionmentioning
confidence: 99%
“…Initially, 491 articles were selected and identified; 10 were repeated, and 479 were excluded by the analysis of their title and abstract. Lastly, two potential articles 3,8 were included, as they met the guidelines proposed for the present systematic research. Based on the chosen descriptors, the scientific data banks were consulted to extract the information made available in being attended, besides fever and mental changes, as the main clinical manifestations to analyze the occurrence of deaths.…”
Section: Resultsmentioning
confidence: 99%